Efeito da Biochanina a na intoxicação induzida por Diquat em camundongos - Nascimento, Ana Carla Silva (2023)
Diquat (DQ) is a herbicide, a pesticide used to control weeds in various crops such as coffee, corn and wheat. Scientific studies have revealed that DQ can cause damage to various organs of animals and humans, with the liver being one of the main targets of this pesticide. Biochanin A (BCA) appears as a natural alternative to prevent the damage caused by DQ, as it is a compound that has antioxidant and anti-inflammatory effects described in the literature, and can be found in several natural sources such as red clover, soy, chickpeas, among others. The aim of this study was to evaluate the effect of previous use of BCA on Diquat-induced intoxication in mice. Female Swiss albino mice (Mus musculus) were divided into 6 groups (saline, BCA 100 mg/kg, DQ, BCA 25 mg/kg + DQ, BCA 50 mg/kg + DQ and BCA100 mg/kg + DQ) (n=8), treated for 12 days. On the 12th day, the animals were intoxicated with DQ 25 mg/kg or saline, intraperitoneally (i.p). After 24 hours of challenge, the animals were euthanized and blood and organs were collected. These tissues were then taken for analysis to determine whether BCA exerted a protective effect against DQ. The animals that received the doses of BCA showed less damage caused by oxidative stress, in addition to having lower concentrations of liver enzymes, which is related to a hepatoprotective effect. An anti-inflammatory effect of BCA can still be observed, while the animals that received only DQ showed greater inflammation, the animals that were pre-treated with BCA showed reduced inflammation, compared to the DQ group. Thus, it was concluded that BCA has antioxidant and anti-inflammatory potential, with consequent hepatoprotection.